Impact of orthognathic surgery on bite force of individuals with repaired cleft lip and palate - Bueno, Patricia Martins (2020)
Introduction: Cleft lip and palate (CLP) frequently leads to a maxillary deficiency, induced by primary reconstructive plastic surgery, often requiring orthognathic surgery (OS) in adulthood. Objective: To evaluate the impact of orthognathic surgery on the stomatognathic system of individuals with repaired CLP by assessing bite force (BF). Material and Methods: Forty individuals were prospectively divided into 2 groups: 1) CON: 20 individuals without CLP (10 male, 10 female, 20y±7.4), 2) CLP: 20 individuals with CLP and with indication for OS (11 male, 9 female, 23.5y±5.9; 10 unilateral; 10 bilateral), BF was evaluated in the immediate preoperative period (PRE), 3 months postoperatively (POST3M) and 6 months postoperatively (POST6M), by means of a gnathodynamometer (IDDK Kratos, Cotia-SP, Brazil). Results: BF of the CLP was significantly lower than that of the CON in all evaluated periods. BF of individuals with CLP was significantly lower in POST3M when compared to PRE and POST6M. Although not significant, BF was increased in POST6M when compared to PRE. A significant increase in BF was observed between POST3M and POST6M. The BF of unilateral and bilateral CLP individuals were statistically similar. Males presented a BF almost twice as high as females. Conclusion: Cleft lip and palate negatively impacts BF. Although BF values increased 6 months after orthognathic surgery, it was still significantly reduced when compared to control individuals, not reaching normative values